Effects of different suboptimal dietary protein levels on growth, nutrient utilization and physio‐metabolic status of Anabas testudineus fingerlings in inland saline water. (1st November 2021) - Talukdar, Avinash; Dharmendra Deo, Ashutosh; Prasad Sahu, Narrotam; Sardar, Parimal; Aklakur, MD; Prakash, Satya
Abstract: A 60‐day feeding trial was conducted to illustrate the effect of suboptimal crude protein (CP) levels on growth and physio‐metabolic status of Anabas testudineus fingerlings reared in inland saline water (ISW) at 8 g/L salinity. Six isoenergetic (16 MJ/kg) and isolipidic (60 g/kg) diets with 240 (T24), 260 (T26), 280 (T28), 300 (T30), 320 (T32) and 340 (T34) g suboptimal CP/kg diet were formulated. Weight gain (%) and specific growth rate were significantly higher ( p  < .05) in T32 and T34 groups. Feed conversion ratio was significantly lower ( p  < .05) in T30 and T32 group than the other groups. The protein utilizing efficiency was significantly ( p  < .05) decreased beyond 320 g CP/kg diet. The protease activity was significantly increased ( p  < .05) up to 320 g CP/kg diet, whereas amylase activity was significantly higher ( p  < .05) in 240–260 g CP/kg diets. The transaminase enzyme activities were significantly higher ( p  < .05), and energy demanding enzymes were significantly lower ( p  < .05) in 300–340 g CP/kg diets. Fish of T24 and T26 groups had lowest ( p  < .05) glycogen, erythrocyte count and total protein with highest ( p  < .05) glucose and antioxidant enzyme activities. In conclusion, feeding 320 g CP/kg diet is recommended for cost‐effective growth of A .  testudineus reared in ISW at 8 g/L salinity.